2021
DOI: 10.1001/jamaneurol.2020.3836
|View full text |Cite|
|
Sign up to set email alerts
|

Microbleeds and the Effect of Anticoagulation in Patients With Embolic Stroke of Undetermined Source

Abstract: The reported associations of cerebral microbleeds with recurrent stroke and intracerebral hemorrhage have raised concerns regarding antithrombotic treatment in patients with a history of stroke and microbleeds on magnetic resonance imaging.OBJECTIVE To characterize microbleeds in embolic strokes of undetermined source (ESUS) and report interactions between microbleeds and the effects of random assignment to anticoagulant vs antiplatelet therapy.DESIGN, SETTING, AND PARTICIPANTS Subgroup analyses of the New App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…With regard to anticoagulation, there were no interactions identified between baseline presence, location or severity of CMBs and rivaroxaban 15 mg daily compared with aspirin for the outcomes of IS, ICH or mortality over 11 months of follow-up in NAVIGATE ESUS participants (n=3699, 11% with CMBs). 111 In particular, there was no suggestion of a treatment effect for the outcome of sICH (participants with CMBs: HR 3.1, 95% CI 0.3 to 30.0; without CMBs: HR 3.0, 95% CI 0.6 to 14.7; interaction p=0.97).…”
Section: Cmbs: Useful Biomarkers In the Era Of Precision Medicine? Management Of Antithrombotic Agentsmentioning
confidence: 90%
“…With regard to anticoagulation, there were no interactions identified between baseline presence, location or severity of CMBs and rivaroxaban 15 mg daily compared with aspirin for the outcomes of IS, ICH or mortality over 11 months of follow-up in NAVIGATE ESUS participants (n=3699, 11% with CMBs). 111 In particular, there was no suggestion of a treatment effect for the outcome of sICH (participants with CMBs: HR 3.1, 95% CI 0.3 to 30.0; without CMBs: HR 3.0, 95% CI 0.6 to 14.7; interaction p=0.97).…”
Section: Cmbs: Useful Biomarkers In the Era Of Precision Medicine? Management Of Antithrombotic Agentsmentioning
confidence: 90%
“… 3 On the other hand, an exploratory analysis of the New Approach Rivaroxaban Inhibition of Factor Xa in a Global Trial Versus ASA to Prevent Embolism in Embolic Stroke of Undetermined Source (NAVIGATE ESUS) trial that compared the direct oral anticoagulant rivaroxaban to the platelet inhibitor aspirin recently showed that CMBs in patients with ischemic stroke may well be a marker of worse clinical outcome in general without implying annulment of a beneficial effect of an intervention. 9 …”
mentioning
confidence: 99%
“…However, anti-coagulation use is known to not only increase the risk of symptomatic intracranial hemorrhage ( 33 ), but some data suggests that the number of CMB in patients with AF increase when patients are placed on oral anti-coagulation ( 2 , 34 ). However, subgroup analyses of the New Approach Rivaroxaban Inhibition of Factor Xa in a Global Trial vs. Aspirin to Prevent Embolism in Embolic Strokes of Undetermined Sources (NAVIGATE ESUS) trial found that while CMB are a marker of increased risk of recurrent stroke and mortality, they do not increase the risk of poor outcomes for patients on rivaroxaban vs. aspirin, which is encouraging ( 35 ).…”
Section: Discussionmentioning
confidence: 99%